Long‐Term Evaluation of Mulch Biowall Performance to Treat Chlorinated Solvents. Issue 1 (5th February 2020) - Walker, Kenneth L.; McGuire, Travis M.; Adamson, David T.; Anderson, R. Hunter
Abstract: Permeable reactive barriers (PRBs), such as mulch biowalls, have been installed at numerous groundwater cleanup sites, and laboratory and field studies have demonstrated biotic and abiotic processes that degrade chlorinated volatile organic compounds (CVOCs) in groundwater passing through these engineered remedies. However, the longevity of mulch biowalls remains a fundamental research question. Soil and groundwater sampling at seven mulch biowalls at Altus Air Force Base (AFB) approximately 10 years after installation demonstrated the ongoing degradation of CVOCs. Trichloroethene was not detected in five of seven groundwater samples collected from the biowall despite upgradient detections above federal drinking water standards. Microbial sampling established the presence of key dechlorinating bacteria and the abundance of genes encoding specific enzymes for degradation, high methane concentrations, low sulfate concentrations, and negative oxidation‐reduction potential, all indicative of highly reducing conditions within the biowalls and favorable conditions for CVOC destruction via microbial reductive dechlorination. High cellulose content (>79%) of the mulch, elevated total organic carbon (TOC) content in groundwater, and elevated potentially bioavailable organic carbon (PBOC) measurements in soil samples further supports an ongoing, long‐lived source of carbon. These results demonstrate the ongoing and long‐term efficacy of the mulch biowalls at Altus AFB. In addition, concentrations of bacteria, TOC, PBOC, and other geochemical parameters suggest a modest impact of the biowalls downgradient. The continued presence of CVOCs downgradient may be attributable to back diffusion from low‐permeability shale. However, the biowalls continue to provide benefits by removing CVOCs in groundwater, thus reducing further CVOC loading to the downgradient, low‐permeability strata.